Is It Important To Integrate Islamic Values In Accounting Education? - Binti Shofiatul Jannah (LPPM ISNJ Bengkalis, 2023)
Various accounting scandals involving the accounting profession are indicated because of the dominance of reason in accounting education. So, this research aims to understand and examine the perceptions of accounting educators about integrating Islamic values into accounting education. An interpretive perspective is used in this qualitative research. Data collection techniques through interviews. In-depth interviews were conducted with three accounting lecturers with open questions. Furthermore, the results of the interviews were transcribed and analyzed using the Miles and Huberman model, namely data reduction, data presentation, and conclusion. Islamic values are essential to be integrated into accounting education. Integrating Islamic values in accounting education includes praying together before learning, reading Quran verses, and practising